The Role of Urban Environment Design on Health During the COVID-19 Pandemic: A Scoping Review - Sara Faedda; Alessandro Plaisant; Valentina Talu; Giulia Tola (Frontiers Media S.A., 2022)
The COVID-19 pandemic has had a significant impact on the ways and times of living and using urban spaces, specifically referring to the dimension of daily life. The restrictive measures introduced during the lockdown periods have necessarily led to a re-evaluation of proximity scale bringing particularly attention to issues relating to public transport and mobility and to the quality and distribution of open public spaces. This scoping review explores the relationship between the urban environment design and health referring to the constraints imposed by the COVID-19 pandemic in the period from 2020 to 2021, with two main objectives: (i) to investigate the recurring urban design topics and issues related to the spatial and social needs stressed by the emergency; (ii) to identify the urban design measures both experienced during the health emergency and proposed in view of a post-COVID urban and territorial planning as they are considered impactful on health promotion. The search strategy was based on a set of keywords searched in two electronic databases which allowed the identification of a total of 1,135 contributions. After defining the eligibility criteria, we proceeded to the screening process concluded with the inclusion of 19 studies. The analysis of the contributions led to the systematization of six main urban topics-and to the corresponding spatial requirements and project proposals-highlighted as relevant and supportive in terms of the promotion of inhabitant's public health: (i) transport, mobility and accessibility; (ii) green and outdoor spaces; (iii) public and pedestrians' spaces; (iv) care services and health network; (v) communications; (vi) public and business services. The resulting framework is useful for guiding healthy city planning toward public policies, tools, regulations, urban measures, and emergency contrast provisions, that contribute to increasing the effectiveness in terms of safety and well-being.